2019
DOI: 10.1088/0256-307x/36/7/070501
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Ferroelectric Phase Transition with Neglectable Tunneling Effect*

Abstract: Due to the obvious deviations of the existing theoretical models from the experimental results of ferroelectric phase transition, a new model is proposed on the basis of the coupling between spontaneous polarization and spontaneous strain in ferroelectrics. The spontaneous polarization and specific heat of ferroelectric phase transition predicted by the model are in better agreement with the corresponding data of triglyceride sulfate, a typical ferroelectric. In addition, the model predicts a new type of ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…These values are comparable to the traditional ferroelectric materials such as PbTiO 3 (∼200 meV) [36,37] and the 2D ferroelectric In 2 Se 3 (66 meV), [5] indicating that an applied gate field can be readily to switch monolayer CuMoP 2 S 6 from the antiferroelectric ground state to two ferroelectric states (with ±𝑃 ).…”
mentioning
confidence: 52%
“…These values are comparable to the traditional ferroelectric materials such as PbTiO 3 (∼200 meV) [36,37] and the 2D ferroelectric In 2 Se 3 (66 meV), [5] indicating that an applied gate field can be readily to switch monolayer CuMoP 2 S 6 from the antiferroelectric ground state to two ferroelectric states (with ±𝑃 ).…”
mentioning
confidence: 52%
“…While the second stage (approximately 1954 to now) mainly focuses on the macroscopic crystalline materials of component heterogeneous distribution, specifically the random distribution of some kinds of elements on the crystal lattice (no symmetry of space translation), also known as the crystals of component random distribution, such as lead magnesium niobate [7][8][9][10] and barium zirconate titanate [11,12] of ferroelectrics (including relaxorferroelectrics and dipole glasses), as well as gold iron, [13] bismuth manganese scandate [14,15] of ferromagnets (including relaxor-ferromagnets and spin glasses), etc. [16][17][18][19][20] After the first stage of researches, a gradually mature theoretical system for ferroelectric and ferromagnetic phase transitions in the crystals of uniformly distributed components has been established, including the phenomenological theories (Weiss molecular field theory, [21,22] Landau theory, [23] Devonshire theory, [24][25][26] etc. ), and the microscopic models (Ising model, [27] Heisenberg model, [28] etc.)…”
Section: Introductionmentioning
confidence: 99%
“…), and the microscopic models (Ising model, [27] Heisenberg model, [28] etc.) as well as the corresponding solution methods (Weiss mean field, [22] Bethe mean field, [29] matrix transformation, [30,31] Wilson momentum space renormalization group theory, [32] and Kadanoff position space renormalization group theory [33] ).…”
Section: Introductionmentioning
confidence: 99%
“…However, for large-scale contact, when the roughness is small, the relationship between the real contact area and the normal load is nonlinear. [21,22] Rubinstein et al [5] believed that for the contact of the surface with small roughness (RMS < 0.1 µm), the nonlinear phenomenon might be related to the evanescent wave, and the measurement error of contact area would be caused by the tunneling effect [27] of light when the real contact area was measured based on the total reflection method. Different from the analysis of Rubinstein et al, Matsuda et al [24,25] compared the effects of vacuum, dry and wet environment on real contact area, and found that the relationship between real contact area and normal load would be related to the existence of fluid between contact interface.…”
Section: Introductionmentioning
confidence: 99%